Analisis Hasil Evaluasi Kinerja Kelompok Jabatan Fungsional Pemeriksa Pajak Kantor Pelayanan Pajak PMA Dua menggunakan Metode Naive Bayes - Agustinus Ryan Wicaksono; Satrio Hadi Wijoyo; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Employee Performance Evaluation is an evaluation process conducted by an agency, both government agencies and private agencies to measure the performance and quality of employees in the agency. PMA Dua Tax Service Office is one of the govenrment agency that run the performance evaluation to measure the performance of the Tax Auditor Functional. However, in the implementation of the performance evaluation, PMA Dua Tax Service Office encountered obstacles where the data variables were used and there were still a lot of scattered data. So it needs accuracy in processing the data used to assess employee performance. Therefore, the author conducted an analysis using naice bayes on the tax audit functional performance evaluation data in onder to fund out how the employee's performance was. The author uses the 2019 employee data as much as 64 data which is used to train the naive bayes model. The resultsof the application of data mining produce an accuracy of 93.75% using the Accuracy Score method and an accuracy of 82,5% using the K-Fold Cross Validation method. The naive bayes model that has been built is also used to predict employee performance in 2020 using 52 data. The dashboard that has been formed has an average score of 80, which means that the dashboard is acceptable and can be used by the PMA Dua Tax Service Office.